Cost-Effectiveness of One-Time Hepatitis C Screening Strategies Among Adolescents and Young Adults in Primary Care Settings. (9th September 2017) - Assoumou, Sabrina A; Tasillo, Abriana; Leff, Jared A; Schackman, Bruce R; Drainoni, Mari-Lynn; Horsburgh, C Robert; Barry, M Anita; Regis, Craig; Kim, Arthur Y; Marshall, Alison; Saxena, Sheel; Smith, Peter C; et al.
Abstract : Risk-based hepatitis C virus (HCV) testing is recommended for young adults. We used simulation modeling to show that routine rapid HCV testing during clinical visits might be cost-effective in settings with a high prevalence of HCV and injection drug use. Abstract: Background: High hepatitis C virus (HCV) rates have been reported in young people who inject drugs (PWID). We evaluated the clinical benefit and cost-effectiveness of testing among youth seen in communities with a high overall number of reported HCV cases. Methods: We developed a decision analytic model to project quality-adjusted life years (QALYs), costs (2016 US$), and incremental cost-effectiveness ratios (ICERs) of 9 strategies for 1-time testing among 15- to 30-year-olds seen at urban community health centers. Strategies differed in 3 ways: targeted vs routine testing, rapid finger stick vs standard venipuncture, and ordered by physician vs by counselor/tester using standing orders. We performed deterministic and probabilistic sensitivity analyses (PSA) to evaluate uncertainty. Results: Compared to targeted risk-based testing (current standard of care), routine testing increased the lifetime medical cost by $80 and discounted QALYs by 0.0013 per person. Across all strategies, rapid testing provided higher QALYs at a lower cost per QALY gained and was always preferred. Counselor-initiated routine rapid testing was associated with an ICER of $71000/QALY gained. Results were sensitive to offer and result receipt rates. Counselor-initiated routine rapid testing was cost-effective (ICER <$100000/QALY) unless the prevalence of PWID was <0.59%, HCV prevalence among PWID was <16%, reinfection rate was >26 cases per 100 person-years, or reflex confirmatory testing followed all reactive venipuncture diagnostics. In PSA, routine rapid testing was the optimal strategy in 90% of simulations. Conclusions: Routine rapid HCV testing among 15- to 30-year-olds may be cost-effective when the prevalence of PWID is >0.59%.